Pengembangan bahan ajar matematika untuk siswa SMP berdasarkan teori belajar ausubel - Rahmita Yuliana Gazali (PYTHAGORAS Jurnal Pendidikan Matematika, 2016)
Penelitian ini bertujuan untuk menghasilkan bahan ajar matematika berdasarkan teori belajar Ausubel untuk siswa SMP berupa lembar kegiatan siswa (LKS), namun terlebih dahulu dikembangkan rencana pelaksanaan pembelajaran (RPP) dan tes prestasi belajar (TPB) dimana RPP dan LKS memenuhi kriteria valid, praktis, dan efektif serta TPB memenuhi kriteria valid, praktis, dan reliabel. Penelitian ini merupakan penelitian pengembangan yang diadaptasi dari model Borg Gall yang terdiri dari tiga langkah utama yaitu studi pendahuluan, desain produk, dan pengembangan dan evaluasi. Kevalidan produk dilihat dari hasil validasi ahli dan mencapai kriteria valid untuk LKS dan sangat valid untuk RPP dan TPB. Kepraktisan produk mencapai kategori sangat praktis ditinjau dari lembar kepraktisan guru dan siswa serta observasi keterlaksanaan pembelajaran. Keefektifan produk ditinjau dari sikap, pengetahuan, dan keterampilan. Hasil uji coba lapangan menunjukkan lebih dari 70% siswa mencapai Kriteria Ketuntasan Minimum untuk pengetahuan dan keterampilan, serta mencapai kriteria baik dan sangat baik untuk ranah sikap.Kata kunci: pengembangan, bahan ajar, teori belajar ausubel Development of mathematics teaching material for junior high school students based on ausubel learning theory AbstractThis research is aimed to produce teaching material of mathematics based on Ausubel learning theory for Junior High School students in the form of student’s activity sheet, but at first the lesson plan is developed and the completeness of learning achievement test, that is the lesson plan and student activity sheet to meet the criteria for a valid, practical, and effective devices and the learning achievement test to meet the criteria for a valid, practical, and reliable devices. This research is the development of a model adapted from Borg  Gall which consists of three main steps such as the preliminary study stage, the stage of product design, and the development and evaluation stages. The validity of the products seen from the results of the validation experts stating that the products reach the valid criteria for student activity sheet and very valid for lesson plan and learning achievement test. The practicality of products seen from the practicality teachers sheet and practicality students sheet and study observation sheet. The effectiveness of the products obtained from attitudes, knowledge, and skills. The results of field trials showed more than 70 % of students achieving mastery Minimum Criteria for knowledge and skills , as well as achieving good and excellent criterion for the attitude sphere .Keywords: development, instructional materials, Ausubel learning theory